2016
DOI: 10.5430/jnep.v7n1p51
|View full text |Cite
|
Sign up to set email alerts
|

Community-based pedagogy of nursing in developing countries: An integrative review

Abstract: Purpose: Community-based nursing education programs have been recognized for innovative pedagogies. Their influence have focused on clinical experiences of students redirected from hospital-based to community settings. However, their implementation, pedagogy, and impact on the quality of nursing education outcomes have not been clearly evaluated. The purpose of this paper was to explore the extent, nature, and quality of community-based nursing education programs in developing countries. Methods: An integrativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 51 publications
0
4
0
2
Order By: Relevance
“…Bu gereklilik, hemşirelik eğitimini hastane temeli eğitimden TTE'ye yönlendiren bir paradigma değişimini de beraberinde getirmektedir (Mtshali, 2011). Toplum temelli hemşirelik eğitimi, hemşirelik öğrencilerinin bireylerin olduğu her yerde, birey ve aile merkezli hemşirelik bakımı vermeyi öğrendiği (Hunt, 2013;Nambozi & Locsin, 2017;Zotti ve ark, 1996), klinik eğitimin hastanelerden çok toplumun olduğu her ortamda uygulandığı, farklı öğrenme ortamları ve stratejileri sunan yenilikçi bir eğitimdir (Carter ve ark, 2005). Toplum temelli hemşirelik, hemşirelikte bir uzmanlık alanı değil tüm hemşirelik uzmanlık alanlarına rehberlik eden bir felsefedir (Zotti ve ark, 1996).…”
Section: Toplum Temelli Hemşirelik Eğitimiunclassified
See 3 more Smart Citations
“…Bu gereklilik, hemşirelik eğitimini hastane temeli eğitimden TTE'ye yönlendiren bir paradigma değişimini de beraberinde getirmektedir (Mtshali, 2011). Toplum temelli hemşirelik eğitimi, hemşirelik öğrencilerinin bireylerin olduğu her yerde, birey ve aile merkezli hemşirelik bakımı vermeyi öğrendiği (Hunt, 2013;Nambozi & Locsin, 2017;Zotti ve ark, 1996), klinik eğitimin hastanelerden çok toplumun olduğu her ortamda uygulandığı, farklı öğrenme ortamları ve stratejileri sunan yenilikçi bir eğitimdir (Carter ve ark, 2005). Toplum temelli hemşirelik, hemşirelikte bir uzmanlık alanı değil tüm hemşirelik uzmanlık alanlarına rehberlik eden bir felsefedir (Zotti ve ark, 1996).…”
Section: Toplum Temelli Hemşirelik Eğitimiunclassified
“…Hemşirelik girişimleri birey, aile ve toplumun değerleri doğrultusunda birey, aile ve sağlık ekibi üyeleri tarafından belirlenir. TTE ile öğrenciler, multidisipliner bir ekibin üyesi olarak kaynakları yetersiz bu alanlarda çalışmaya hazırlanırlar (Nambozi & Locsin, 2017;Hunt, 2013).…”
Section: Toplum Temelli Hemşirelik Eğitimiunclassified
See 2 more Smart Citations
“…For the community settings, Nambozi [4] integrate reviewed 38 articles related to the community-based pedagogy of nursing in developing countries and found the major domain of five themes was to facilitate the nursing students to be the competent nurses bridging their academic learning with the clinical works by using community partnership relationship. In terms of the roles of facilitating, Doghtrey [5] conducted the literature review of three cases with a mixed method of 46 discrete and practical facilitation activities and identified that communication and relationshipbuilding were the key elements of developing evidences-based practice of facilitation along with the internal and external factors.…”
mentioning
confidence: 99%